Patient satisfaction: a key concept for evaluating and improving nursing services - Yfantopoulos, John N.; Lanara, Vassiliki A.; Lemonidou, Chryssoula; Merkouris, Anastasios (My University, 1999)
Aims The main purpose of this review was to explore the meaning of patient satisfaction and present the theoretical background and the definitions which developed in nursing. Background Today, there is an increasing interest in patient satisfaction which is considered a valid indicator of the quality of care. Origins of information An extensive literature review was performed by using the MEDLINE database. Data analysis Data was classified and analysed by using the content analysis approach. Key issues The principal finding of this review was the lack of attention to the meaning of patient satisfaction, the development of theoretical frameworks and the psychometric properties of the developed instruments. Conclusions Nurses need to develop valid and reliable instruments to measure patient satisfaction in order to improve the quality of care and make their work visible.